2002
DOI: 10.1159/000067560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intrauterine Myelomeningocele Repair on the Incidence of Shunt-Dependent Hydrocephalus

Abstract: Background: Intrauterine myelomeningocele repair (IUMR) was first successfully performed in 1997. Preliminary reports suggest that this procedure reduces the incidence of shunt-dependent hydrocephalus when compared to conventional postnatal therapy. However, the existing cohort of IUMR patients has not yet been systematically compared to a comparable group of conventionally treated controls. Methods: Patients 1 year old or greater who had undergone IUMR at either Vanderbilt University or the Children’s Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
3
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 14 publications
4
87
3
4
Order By: Relevance
“…4 The clinical outcomes of in utero surgery have suggested clear improvement in some neurological lesions, namely in the reversal of ectopic cerebellar tonsils of the MMC-associated Chiari malformation, decreasing it from 95 to 38%, with a consequent reduction in the need for a ventricular shunt from 91 to 59%. 3,[31][32][33][34] In contrast, deficits in the lower limbs and in urodynamic function in patients submitted to MMC correction, through either fetal or classic postnatal surgery, were similar to those of controls. 14,30,27 Attending to these data, the potential benefits of in utero repair of MMC are under scrutiny in a randomized trial designed to compare the clinical outcomes of patients with MMC treated with either fetal or postnatal surgery.…”
mentioning
confidence: 83%
“…4 The clinical outcomes of in utero surgery have suggested clear improvement in some neurological lesions, namely in the reversal of ectopic cerebellar tonsils of the MMC-associated Chiari malformation, decreasing it from 95 to 38%, with a consequent reduction in the need for a ventricular shunt from 91 to 59%. 3,[31][32][33][34] In contrast, deficits in the lower limbs and in urodynamic function in patients submitted to MMC correction, through either fetal or classic postnatal surgery, were similar to those of controls. 14,30,27 Attending to these data, the potential benefits of in utero repair of MMC are under scrutiny in a randomized trial designed to compare the clinical outcomes of patients with MMC treated with either fetal or postnatal surgery.…”
mentioning
confidence: 83%
“…The simplified technique also allowed better preservation of the spinal cord cytoarchitecture. Several previous studies on the intrauterine correction of myelomeningocele had already suggested that prenatal correction led to a better preservation of the spinal cord and better clinical results (10)(11)(12)(13) .The MOMS study demonstrated that the intrauterine correction reduced the need of ventriculoperitoneal shunting from 82 to 40% comparing postnatal with prenatal correction, respectively. That study also showed better cognitive and motor skills up to 30 months of age in the group submitted to prenatal correction (6) .…”
Section: Discussionmentioning
confidence: 94%
“…That study also showed better cognitive and motor skills up to 30 months of age in the group submitted to prenatal correction (6) . As to the uterine approach, some studies showed that open surgery greatly increased the risk of premature labor and maternal complications (6,10,12) . In the MOMS study, average gestational age at birth was 34.1 weeks in cases of prenatal surgery versus 37.3 weeks in postnatal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recent data show a decrease in the rate of Chiari II malformation and subsequent hydrocephalus in patients in whom the spinal defect is repaired in utero. [8][9][10] However, this remains controversial. The open system of cerebrospinal fluid (CSF) circulation resulting from open spinal dysraphism (with fluid production in the ventricular system and passage down and out through the spinal defect) is thought to play a central role in hindbrain descent and subsequent hydrocephalus.…”
Section: Pathogenesismentioning
confidence: 99%